The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2001
DOI: 10.1590/s0101-81752001000300009
|View full text |Cite
|
Sign up to set email alerts
|

Biologia e ecologia de Anthodioctes moratoi Urban (Hymenoptera, Megachilidae, Anthidiini) em matas contínuas e fragmentos na Amazônia Central, Brasil

Abstract: ABSTRACT. Biology and ecology ofAnlflOdioctes moratoi Urban (Hymenoptera, Megachilidae, Anthidiini) in continuous forests and forest fragments in Central Amazonia, BraziJ. An/hodioc/es mora/oi Urban, 1999 was described based on specimens collecled in lhe slate of Amazonas during a study ofthe ecology oftrap-nesting bees and wasps. Sampling was done between 1988 and 1990 north ofManaus, in areas of the "Forest Fragment Biological Dynamics Project". Wooden lrap-nests were seI in dilTerent heights inside continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
12

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 13 publications
(1 reference statement)
1
14
1
12
Order By: Relevance
“…Aguiar & Garófalo (2004) found significant correlations between number of nests occupied by Centris (Hemisiella) tarsata Smith and monthly precipitation in the State of Bahia. However, in a study done in the Central Amazon region, no significant correlation was found between rainfall and number of nests occupied by Anthodioctes moratoi Urban (Morato 2001b). In general, although no significant correlation was found between temperature, rainfall, and nesting frequency of other species in our study, the climate directly influenced environmentrelated variables such as system productivity (Begon et al 1996) and the resources availability for nest construction and maintenance (mud, preys and pollen).…”
Section: Discussioncontrasting
confidence: 67%
“…Aguiar & Garófalo (2004) found significant correlations between number of nests occupied by Centris (Hemisiella) tarsata Smith and monthly precipitation in the State of Bahia. However, in a study done in the Central Amazon region, no significant correlation was found between rainfall and number of nests occupied by Anthodioctes moratoi Urban (Morato 2001b). In general, although no significant correlation was found between temperature, rainfall, and nesting frequency of other species in our study, the climate directly influenced environmentrelated variables such as system productivity (Begon et al 1996) and the resources availability for nest construction and maintenance (mud, preys and pollen).…”
Section: Discussioncontrasting
confidence: 67%
“…We confirmed this prediction with the results obtained for A. megachiloides, although this species had low frequency of occurrence in the studied area, occupying a greater number of nests in smaller areas. Another Anthodioctes species, A. moratoi established a greater number of nests in larger areas (continuous forests) than in forest remnants in Central Amazon (Morato 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Studies with solitary bees demonstrate the presence of fungi in the nests as the main cause of death (Morato, 2001;Camarotti-deLima and Martins, 2005). Although T. diversipes is a widespread species, the studied nests are from areas of Atlantic Forest with high rainfall rates, in particular during the summer, which most likely contributes to the proliferation of fungi.…”
Section: Discussionmentioning
confidence: 99%